The Relationship between Demographic Factors and Gender Role Attitudes in Women Referring to Mashhad Health Care Centers in 2014 - Elham Fazeli; Nahid Golmakani; Ali Taghipour; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2015)
Background & aim:  Gender roles are affected by biosocial and cultural factors. These roles have significant impacts on one's professional, social, and family life. Therefore, given the recent changes in gender roles in Iran, we aimed to determine the relationship between demographic factors and gender role attitudes among women. Methods:This cross-sectional study was conducted on 712 females, selected via stratified sampling. Data were collected using a demographic checklist and a gender role questionnaire including 2 sections: gender role stereotypes and gender egalitarianism. The validity of this questionnaire was confirmed by content validity and its reliability was verified by internal consistency (α=0.77). For data analysis, ANOVA and correlation coefficient tests were performed, using SPSS version16. Results: The mean scores of gender role stereotypes and egalitarianism were 29.55±4.33 and 112.55±14.64, respectively. Stereotypic and egalitarian attitudes were significantly correlated with age, family size, duration of marriage, women's age at first childbirth, educational level, intentions to pursue education in future, and occupational status. Conclusion: As to the finding, gender role attitudes were influenced by social, economic, and demographic factors in Iran. By paying attention to these factors, we can implement proper interventions in order to promote personal and social health among women.